2018
DOI: 10.1371/journal.pone.0197620
|View full text |Cite
|
Sign up to set email alerts
|

First description of Echinococcus ortleppi and cystic echinococcosis infection status in Chile

Abstract: Cystic echinococcosis (CE), a parasitic disease caused by the cestode Echinococcus granulosus sensu lato (s.l.), is a worldwide zoonotic infection. Although endemic in Chile, information on the molecular characteristics of CE in livestock remains scarce. Therefore we aimed to describe the status of infection with E. granulosus s.l. in cattle from central Chile and also to contribute to the study of the molecular epidemiology of this parasite. According to our results, the prevalence of CE is 18.84% in cattle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
1
12
0
3
Order By: Relevance
“…A recent study in Chile, found that the proportion of organs infected with E. granulosus varied among geographical locations [ 36 ]. These authors have shown that of the genotyped cysts, belonging to 47.95% of E. granulosus -infected animals, most were identified as E. granulosus ( s.s. ) as has previously been reported in cattle in Chile [ 26 ]; this species is also the most common worldwide [ 37 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A recent study in Chile, found that the proportion of organs infected with E. granulosus varied among geographical locations [ 36 ]. These authors have shown that of the genotyped cysts, belonging to 47.95% of E. granulosus -infected animals, most were identified as E. granulosus ( s.s. ) as has previously been reported in cattle in Chile [ 26 ]; this species is also the most common worldwide [ 37 ].…”
Section: Discussionsupporting
confidence: 66%
“…Echinococcus granulosus ( s.l. ) genotyping in hydatid cyst samples was determined as previously reported [ 26 ]. Briefly, DNA was extracted from fertile, infertile and small hydatid cysts from both livers and lungs.…”
Section: Methodsmentioning
confidence: 99%
“…While the fertility rate of E. ortleppi bovine cysts is very high (>90%), for E. granulosus it normally does not exceed 30% in this host species [2,[16][17][18]. Moreover, E. ortleppi develops preferentially in lungs, whereas E. granulosus bovine cysts locate in both liver and lungs [19][20][21][22]. Therefore, E. granulosus and E. ortleppi bovine cysts offer the opportunity to comparatively assess two related species with different degrees of adaptation to a single host species.…”
Section: Introductionmentioning
confidence: 99%
“…Términos ontológicos del proceso biológico, función molecular y subcategorías de componentes celulares de genes asociados con proteínas del parásitos identificadas en el fluido de un quiste hidatídico mediante Blast2Go. G3, G5 y G6) (Manterola et al, 2008;Espinoza et al, 2014;Alvarez Rojas et al, 2017;Corrêa et al, 2018;Hernández et al, 2019); puesto que la existente (Providean Hidatil EG 95Ò), fue desarrollada por utilizando una pequeña fracción proteica de la membrana exterior del parásito; por lo cual presenta una serie de limitaciones, por ejemplo no otorgar similar cobertura en otros genotipos como G6 y G7, pues fue desarrollada para G1; y no da cobertura a la gran variabilidad de haplotipos descritos (Chow et al, 2008;Alvarez Rojas et al, 2013).…”
Section: Discussionunclassified